THE EFFECT OF WORK ENVIRONMENT, WORK LOAD AND WORK STRESS ON EMPLOYEE PERFORMANCE OF PT. GIRVI MAS - Calista; Yunata, Sintia; Yanto, Janetty Su; Rostina, Cut Fitri; Fauzi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
performance at PT Girvi Mas. Data were collected through questionnaires distributed to 110 respondents and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, as well as t-tests and F-tests. The results indicate that the work environment has a positive and significant impact on employee performance. In contrast, workload and stress negatively affect performance in a significant way. Together, these three variables explain 37.6% of the variance in employee performance, while the remaining portion is influenced by factors beyond the scope of this study. These findings align with previous research which suggests that a comfortable work environment enhances performance, whereas excessive workload and high stress levels tend to reduce it. Therefore, it is recommended that PT Girvi Mas foster a supportive workplace atmosphere, balance workloads appropriately, and implement stress management strategies to improve employee performance